Pendekatan Multiple Intelligences dalam Menumbuhkembangkan Kompetensi Psikososial Siswa (Studi Deskriptif pada SDIT Quantum Scholl Banda Aceh) - Nur Afifah (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2022)
Multiple Intelligences besides perfecting and developing the definition of intelligence, it also enriches learning methods. As we realize that in every human being produces intellectual diversity and different levels of development. Education should be able to develop various potentials that exist in children, one of which is psychosocial competence. The problem that currently occurs is that the competencies possessed by students, especially psychosocial competencies, are experiencing a decline, with the Multiple Intelligences approach it will be easy to develop these aspects. The purpose of this study was to determine the initial psychosocial competencies of SDIT Quantum School Banda Aceh students, the Multiple Intelligences approach that was carried out in developing the Psychosocial competencies of SDIT Quantum School students in Banda Aceh, and the final competencies achieved by students after using the Multiple Intelligences approach at SDIT Quantum School Banda Aceh. This research is a field research using qualitative methods. Data was collected through document review, interviews and documentation, then the data was analyzed through descriptive-qualitative. The results of the study found that the initial competence of SDIT Quantum School Banda Aceh students in accordance with the qualifications obtained from teachers through a report card review was categorized as good and still needed improvement. After using several approaches such as Brain Evo (Dermatoglyphics Multiple Intelligence Analysis), Talent Focus, Market Day, Family Gathering, Q-RAC (Quantum Ramadhan Activity), D' Survival Camp, Environment Day, Smart Parenting, PHBI (Islamic Holiday Celebration) , Cherity Day (Social Visit), Habit Training and efforts made by SDIT Quantum School to improve the education of students' attitudes, knowledge and skills, the final psychosocial ability of SDIT Quantum School Banda Aceh students has increased from year to year seen from the study of psychosocial aspects of report cards. which is contained in the 8 values of SEMANGAT and aspects of social ability (KI-2) in the 2013 Curriculum, the increase that occurs due to the implementation of the best process, namely Multiple Intelligences which is applied in every program at SDIT Quantum School Banda Aceh.